2013
DOI: 10.1080/07325223.2013.778673
|View full text |Cite
|
Sign up to set email alerts
|

Supervision by Doctoral Students: A Study of Supervisee Satisfaction and Self-Efficacy, and Comparison with Faculty Supervision Outcomes

Abstract: Satisfaction with supervision and perceived self-efficacy scores reported by master's-level supervisees across seven Council for Accreditation of Counseling and Related Educational Programs(CACREP)-accredited counseling programs were analyzed. Supervisees of doctoral students reported a mean satisfaction score of 26.94 ("good to excellent") on a range of possible scores from 8 (low) to 32 (high) and a mean self-efficacy score of 173.00 ("slightly to moderately agree that they have confidence in performing vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
4
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
(44 reference statements)
0
6
4
1
Order By: Relevance
“…Consistent with our findings, Gazzola et al (2014) found that supervisors-in-training experience various benefits from supervising counselling trainees, including developing their professional identity. We would therefore extend existing recommendations that have cited the benefits of doctoral students providing supervision (Fernando, 2013; Walsh et al, 2017). In addition, we invite educators to consider how maintaining doctoral supervisory responsibilities during times of crisis can offer an important source of consistency amid uncertainty, provide mutual support (Fernando, 2013), and sustain learning for both parties when other resources have been reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our findings, Gazzola et al (2014) found that supervisors-in-training experience various benefits from supervising counselling trainees, including developing their professional identity. We would therefore extend existing recommendations that have cited the benefits of doctoral students providing supervision (Fernando, 2013; Walsh et al, 2017). In addition, we invite educators to consider how maintaining doctoral supervisory responsibilities during times of crisis can offer an important source of consistency amid uncertainty, provide mutual support (Fernando, 2013), and sustain learning for both parties when other resources have been reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Correlations between the five subscales of the CSBQ and the three subscales of the CASES, developed by Lent et al (2003), were also examined. Previous studies (Bernard & Goodyear, 2004; Cashwell & Dooley, 2001) noted that supervision affects counseling self-efficacy, but such studies did not identify what aspects of supervision or supervisors lead to this impact (Fernando, 2013). The present study attempted to examine whether certain types of behaviors of supervisors are closely related with the self-efficacy of counselors.…”
Section: Discussionmentioning
confidence: 99%
“…Faculty evaluations of counselors-in-training occur in academic (e.g., course grades) and interpersonal contexts; including interactions during supervision in practicum and internships, and interactions in and outside of class (Ziomek-Daigle & Christensen, 2010). As counselor educators-in-training, doctoral students have opportunities to serve in evaluative roles as teaching assistants and supervisors of master's level students (Scarborough, Bernard, & Morse, 2006;Fernando, 2013). As part of these roles, doctoral students hold gatekeeping responsibilities (CACREP, 2016;Limberg et al, 2013).…”
mentioning
confidence: 99%